Analisis Kapasitas Container Yard Berdasarkan Throughput Study Case : PT. Multi Terminal Indonesia cabang Halal Logistics dan Cold Storage - Astuti, Dyah Ayu; Widyatmoko, Bimo; Herdian, Tedy (Jurnal Sistem Transportasi & Logistik, 2022)
PT. Multi Terminal Indonesia subdivision Halal Logistics and Cold Storage is a company engaged in the field of logistics service. This research the authors are doing analysis of capacity container yard that has a percentage of yard occupancy ratio over 50% by 2021 means warning overcapacity and it will lead to loading activities in the field became ineffective. The purpose if this research to know throughput container growth in the domestic field and know the field capacity for the next 5 years, so this kind of research is a quantitative with a statistic data analysis. On this study the author uses forecasting methods with techniques used in which normal time series data plot and browser error analysis to determine the forecasting methods to be used. The research uses the type of population data because it uses the 5 years field production report historical data. Based on the miscalculation of the browser by comparison of the 4 kinds of forecasting methods in the fourth error rate, with an 11% MAPE model for the decomposition model method . Based on the forecasting with decomposition method is known throughput through the container for the next 5 year in 2022-2026 earned throughput average yield of 21,925 teus with an average percentage of yard occupancy ratio is in the rate average 61% meaning warning overcapacity field capacity.